An Experimental Investigation into the Flow Properties of Pharmaceutical and Detergent Powders - Garg, Vivek (My University, 2017)
This thesis presents results of an investigation into the flow properties of six popular pharmaceutical powders (Active Pharmaceutical Ingredient: Lactose and Paracetamol, Excipients: Calcium Sulphate, Di-Calcium Phosphate, Magnesium Tri-Silicate and Starch) and one sample of detergent powder and the effects of the same on designing storage facilities with and without considering the influence of time consolidation. Several processing industries face challenges of no flow (arching), inadequate flows, improper powder compaction, segregation etc. due to the lack of fundamental understanding of powder flow properties and their effects on selection of hopper half-angles and outlet sizing. Physical properties such as particle size, specific surface area, porosity, density was investigated. Flow properties (both instantaneous and time consolidation) of all the powder samples were tested on Powder Flow Tester (ring shear tester), manufactured by Brookfield, USA. It was observed, after the time consolidation test, Paracetamol changed its flow characteristics from “cohesive” to “very cohesive”, Lactose from “easy flowing” to “very cohesive”, Starch from “easy flowing” to “cohesive”, Detergent from “free flowing” to “cohesive” whereas other powders (Calcium Sulphate, Di-Calcium Phosphate, Magnesium Tri-Silicate) did not change their flowability characteristics. Using the flow function and the wall friction data, hopper half angle and hopper outlet dimensions were estimated. The results showed that the powders such as Paracetamol, Detergent, Calcium Sulphate and Magnesium Tri-Silicate requires wider hopper outlet dimension. For a good design, the engineer is recommended to carry out necessary flow property testing with and without time consolidation effects into consideration for designing practical storage or feeding systems to achieve desirable mass flow condition.
ME-Thermal Engineering
Keywords: Flow property; Pharmaceutical powder; Detergent powder; Hopper design